CARA MUDAH MEMPELAJARI HURUF KANJI JEPANG - I Gusti Ayu Niken Launingtia (Program Magister Linguistik Universitas Udayana, 2015)
Writing system is used to represent or denote something with something else. This study was aimed at kanji in the Japanese language as a form of writing system, in addition to hiragana and katakana. This study was descriptive qualitative. The object of this study is kanji made by the Japanese language learners in Bunutan, Kedewatan. In order to minimize the difficulties in writing kanji, the learners need to understand the meaning of its constituent elements named the origin of the formation, parts of kanji (bushu??) and their meanings. The theory of sign proposed by Pierce was used in analyzing the data. Some aspects were analyzed including icon, index, and symbol in the scratch of kanji made by the learners. The result of this study shows that the Japanese language learners faced some difficulties in writing kanji. The difficulties were found when the learners tried to remember the way to start and write the correct scratch of kanji.